PENGARUH SARANA/PRASARANA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SURI SENIA PLASMATARUNA, PMKS TALIKUMAIN ROKAN HULU - Dinti Khaisara; Sri Kartikowati; Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: Employee performance is a very valuable company asset that must be managed well by the company to give maximum contribution. The purpose of this study is to determine the facilities / infrastructure and organizational commitment effect significanlyt on employee performance at PT. Suri Senia Plasmataruna, PMKS Talikumain Rokan Hulu. The sample of the research is the employees of the company in the Maintenance Section, Sorting and Processes A and B totaling 83 people. Data is obtained by using documentation technique and questionnaire. Data than is analyseid using descriptive statistics: employee performance analysis, facilities/infrastructure and organizational commitment. The results show of facilities/infrastructure and organizational commitment significant effect on employee performance in PT. Suri Senia Plasmataruna. From these results expected PT. Suri Senia Plasmataruna can improve employee performance with one of the ways is to improve facilities/infrastructure and organizational commitment of employees. If employee performance increases then it will be profitable for the company.Keywords: Performance, Facilities / Infrastructure, Organizational Commitment.